Analisis Strengths, Weaknesses, Opportunities, dan Strategi Email Marketing Dalam Pemasaran - Baitulloh, Sabit; Sulistyowati, Sulistyowati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Nowadays, the role of digital marketing is crucial in a company's marketing strategy. One of the efficient digital marketing elements is email marketing. Email marketing is a marketing strategy in which the distribution and offering of product information is sent via consumer email addresses. This research aims to analyze email marketing strategies using the SWO analysis approach, as well as strategies in achieving marketing goals. Through a comprehensive literature review, this research will identify strengths, weaknesses, opportunities and strategies in utilizing email marketing. Email marketing has strengths including: a) Facilitate Communication; b) Introduce Company Profile; c) Become a Publication Tool; d) Easy to Provide Information; e) Create a Professional Impression; f) Find Partners; g) Can Reach Potential Customers From Anywhere; h) Impact Can Be Immediately Felt; i) The Process and Results Are Easy to Measure; and ii) Processes and Results are Easy to Measure; and j) Provide Multiple Effects. While among the weaknesses are: a) Messages/Emails Sent End up in the Customer's Spam Folder; b) Time-delays that result in delays in sending messages/Emails; c) Email is not owned by everyone/customers.